Penerapan Ice Breaking Dalam Meningkatkan Hasil Belajar Dan Menumbuhkan Semangat Siswa SMP Darma Medan - Nilam Sari; Siti Rakiyah; Hasni Suciawati; Nova Putri Idaman Br Ginting (BADAN PENERBIT STIEPARI PRESS, 2024)
This activity aims to help Darma Middle School students improve their learning outcomes and foster enthusiasm through the application of icebreaking in learning. By implementing icebreaking, it is hoped that it can build a learning atmosphere that is fun, dynamic and full of enthusiasm and not monotonous. Icebreaking is one solution to keep students' enthusiasm high in participating in learning, so that students are motivated and students focus again on learning. This implementation of icebreaking is carried out at the beginning of every lesson in class and in between lessons when students start to lose focus on learning. The PKM team tried to apply a learning method that included ice-breaking to find out how the optimal application of this method could improve learning outcomes and foster students' enthusiasm for learning. The icebreakers used are games or games that are accompanied by body movements. Based on the results of observations over three days, the implementation of icebreaking was quite optimal in fostering student enthusiasm for learning and from the tests given, it was found that there was an increase in student learning outcomes at Darma Medan Middle School.